Implementation of CV Sentosa Abadi Steel Website Redesign Based on Double Diamond and SDLC Prototyping Model - Marcello Hamasias Dwi Greatajoy Purnomo; Anita Safitri (Universitas Negeri Surabaya, 2025)
This research aims to redesign the CV Sentosa Abadi Steel website to improve the quality of appearance, ease of access to information, and user satisfaction. The approach used in the design process is the Double Diamond framework which consists of four stages: Discover, Define, Develop, and Deliver. In addition, the website development process is carried out using the Software Development Life Cycle (SDLC) Prototyping model, which is iterative and involves direct feedback from internal company parties. The Discover stage is done through observation of the old website, and interviews with the CEO and marketing staff. The Define stage is used to formulate system requirements. At the Develop stage, researchers created wireframes and mockups that were adjusted based on the validation results. The Deliver stage is the process of finalizing the design that is ready to be implemented. Implementation is done through the WordPress platform with the help of plugins such as Elementor, Blocksy, and WPForms. Evaluation was carried out using the usability testing method based on five indicators from Nielsen, namely Learnability, Efficiency, Memorability, Error, and Satisfaction, which were measured through questionnaires to five regular customers of CV SAS. The test results show an average score of 3.68 on a scale of 4, which is categorized as Very Good, so it can be concluded that the website has fulfilled the usability aspects and is ready to be used as a medium for company information and promotion.